Cul-de-sac : [large type] a novel - Fielding, Joy (Thorndike Press, a part of Gale, a Cengage Company, 2021)
"Someone on this quiet cul-de-sac will be shot dead. Will it be Maggie, the perfectionist wife, or Craig, the husband who can't quite live up to her expectations? Maybe it will be Nick, an oncologist, or his wife, Dani, a successful dentist, both with secrets of their own. Or Julia, a widow, whose grandson has moved in with her, introducing unsavory habits and acquaintances into her quiet existence. Then there's Olivia and Sean. Having lost his job, Sean is depressed and drinking heavily. And what of the newlyweds, Aiden and Heidi, whose marriage is already on the rocks? All harbor secrets. All bear scars. And all have access to guns. Not all will survive the night"--